Crucial role of oncogenic KRAS mutations in apoptosis and autophagy regulation: therapeutic implications - Ferreira, Anabela (2022)
KRAS, one of the RAS protein family members, plays an important role in autophagy and apoptosis, through the regulation of several downstream effectors. In cancer cells, KRAS mutations confer the constitutive activation of this oncogene, stimulating cell proliferation, inducing autophagy, suppressing apoptosis, altering cell metabolism, changing cell motility and invasion and modulating the tumor microenvironment. In order to inhibit apoptosis, these oncogenic mutations were reported to upregulate anti-apoptotic proteins, including Bcl-xL and survivin, and to downregulate proteins related to apoptosis induction, including thymine-DNA glycosylase (TDG) and tumor necrosis factor (TNF)-related apoptosis-inducing ligand (TRAIL). In addition, KRAS mutations are known to induce autophagy in order to promote cell survival and tumor progression through MAPK and PI3K regulation. Thus, these mutations confer resistance to anti-cancer drug treatment and, consequently, result in poor prognosis. Several therapies have been developed in order to overcome KRAS-induced cell death resistance and the downstream signaling pathways blockade, especially by combining MAPK and PI3K inhibitors, which demonstrated promising results. Understanding the involvement of KRAS mutations in apoptosis and autophagy regulation, might bring new avenues to the discovery of therapeutic approaches for CRCs harboring KRAS mutations.